2022
DOI: 10.3389/fonc.2022.1019009
|View full text |Cite
|
Sign up to set email alerts
|

Ensemble learning based on efficient features combination can predict the outcome of recurrence-free survival in patients with hepatocellular carcinoma within three years after surgery

Abstract: Preoperative prediction of recurrence outcome in hepatocellular carcinoma (HCC) facilitates physicians’ clinical decision-making. Preoperative imaging and related clinical baseline data of patients are valuable for evaluating prognosis. With the widespread application of machine learning techniques, the present study proposed the ensemble learning method based on efficient feature representations to predict recurrence outcomes within three years after surgery. Radiomics features during arterial phase (AP) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 42 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…Recently, a few studies have shown the potential utility of automated segmentation-based CT or MRI radiomics in predicting postsurgical recurrence of HCC [ 28 , 29 ]. For instance, Wang et al employed a DL model to automatically segment tumors on arterial phase images in the external cohort ( n = 31) and reported that an MRI-based radiomic-clinical model achieved good accuracy for predicting postsurgical recurrence [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a few studies have shown the potential utility of automated segmentation-based CT or MRI radiomics in predicting postsurgical recurrence of HCC [ 28 , 29 ]. For instance, Wang et al employed a DL model to automatically segment tumors on arterial phase images in the external cohort ( n = 31) and reported that an MRI-based radiomic-clinical model achieved good accuracy for predicting postsurgical recurrence [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the previous traditional models may fail to show the goodness of fitting or make accurate predictions. Machine learning could train algorithms to detect and recognize complex patterns and adapt to more complex nonlinear relationships, thus it might be superior than the traditional models in medical research (25). In our study, machine learning algorithms, including normal machine learning, Boosting, Bagging, Stacking, and simple deep learning were used and compared on RFS and OS outcomes of HCC patients received PA-TACE.…”
Section: Discussionmentioning
confidence: 99%
“…The rise of artificial intelligence (AI) technology has also brought many new machine learning strategies to predict patient prognosis. In recent researches, several ensemble learning strategies, including Boosting and Bagging algorithm have been developed for HCC and achieved encouraging results (25)(26)(27). Different from other machine learning methods that typically apply one model or one algorithm to a specific task, ensemble learning performs greater flexibility in model selection.…”
Section: Introductionmentioning
confidence: 99%
“…By integrating clinical features into the predictive model, superior prognostic performance was realized with a C-index of 0.733-0.801. Several similar studies employed various machine learning modeling methods, including random forest and SVM [20,25,27,50], to establish predictive models and achieved remarkable results in predicting HCC recurrence, with area under the receiver operator characteristic curves (AUCs) ranging from 0.834 to 0.948. These advancements facilitate a more precise evaluation of recurrence in HCC patients following surgical resection.…”
Section: Surgical Therapy For Malignant Liver Tumorsmentioning
confidence: 99%